A new strategy for yacht ports in Greece under present austerity programmes. (1st January 2012) - Anastasaki, E.N.; Moutzouris, C.I.
The paper shows that yacht ports in Greece are characterised by their excessive number and their expensive construction. Moreover, these ports are scattered all along Greek coast. Admittedly, the locations selected are good. The research we have undertaken has asserted that the current exclusive focus of government on constructing new yacht ports is a waste of resources and this does not suit the style, the size and the psycho-synthesis of the people of this country. The paper, in addition, focuses on how suitably equipped 'zones' have to be formed within the existing harbour installations so that to serve ultimately and effectively leisure crafts. This is the innovative element we have contributed as these zones represent a new strategy in the development of a truly National System of Yacht Ports, traditionally called Marinas. Under present austerity programmes, privatisation of yacht ports is considered by this paper as both optimistic and effective in economic terms.